Influencia de la temperatura de recocido en las películas de Nitruro de tántalo (TaN) sobre la estructura y rugosidad - Pflucker Hilario, Benjamin Orlando (2018)
ABSTRACT Thin films based on tantalum Ta and tantalum nitride TaN, are known for their excellent properties such as mechanical hardness, corrosion resistance and are used in a wide range of industrial, medicinal and hard materials coating applications. The objective of the present work was to determine if there is influence of the annealing temperature of thin films of TaN synthesized by magnetron sputtering with direct current on the structure and roughness. The films of Ta and TaN were deposited on silicon wafers (111) by the reactive magnetic sputtering technique with a direct current source, using a tantalum target, a mixture of argon and nitrogen gases and the films were synthesized at the temperature of 300 °C for a time of 10 minutes. Then the films were annealed in the range of 500 °C to 800 °C in a high vacuum oven in an Argon atmosphere every 100 °C for the time of 1 hour. The structure was evaluated with an X-ray diffractometer and the roughness with an atomic force microscope. The structure remains constant but the intensity of the characteristic diffraction peaks increases as the annealing temperature increases, the roughness increases from 0.0913 nm to 1.950 nm and the crystal size also increases from 39.91 Å to 73.10 Å as the annealing temperature increases. Thin films of TaN were obtained by the DC reactive magnetic spray technique and the structure did not change, however, the roughness increased as the annealing temperature increased due to the fact that the particles are in a weak quantum confinement which causes the increase of said size but it does not affect the crystalline ordering.